Biogeographic and phylogenetic effects on feeding resistance of generalist herbivores toward plant chemical defenses. Issue 1 (1st January 2013) - Craft, Jonathan D.; Paul, Valerie J.; Sotka, Erik E.
Abstract : Many terrestrial and most marine herbivores have generalist diets, yet the role that evolutionary history plays in their foraging behaviors is poorly documented. On tropical hard‐bottom reefs, generalist fishes and sea urchins readily consume seaweeds that produce lipophilic secondary metabolites. In contrast, herbivores on temperate reefs less commonly encounter seaweeds with analogous metabolites. This biogeographic pattern suggests that tropical herbivores should evolve greater feeding resistance to lipophilic defenses relative to temperate herbivores, but tests of this biogeographic pattern are rare. We offered lipophilic extracts from nine subtropical seaweeds at two concentrations to sea urchins (four subtropical and three cold‐temperate populations) and quantified urchin feeding resistance. Patterns of feeding resistance toward lipophilic defenses were more similar within genera than across genera of urchins, indicating a substantial role for phylogenetic history in the feeding ecology of these generalist herbivores. The biogeographic origin of urchins also influenced feeding resistance, as subtropical species displayed greater feeding resistance than did temperate species. Similarly, a subtropical population of Arbacia punctulata had greater feeding resistance for Dictyota and Stypopodium extracts relative to temperate A. punctulata . We conclude that evolutionary history plays a more central role in the foraging ecology of generalist herbivores than is currently appreciated.